JOHN LOCKE’S THEORY OF KNOWLEDGE IN RELATION TO THE BATAGWENDA PEOPLE. A CASE OF KICHECHE SUB-COUNTY, KITAGWENDA DISTRICT, UGANDA. - Ampaire , Innocent (Student's Journal of Health Research Africa, 2024)
Background Knowledge is a set of mental and psychological capacities that make mankind a unique, morally different creature. Although all the created may have capacities of reproduction, self-care, and memory, it is only human beings who are self-conscious, rational, and autonomous, can use language, and are responsible for their actions. This study aimed to examine the theory of knowledge according to John Locke about the Batagwenda people of Kicheche Sub-County, Kita Gwenda district, Uganda. Methods An explorative case study design with qualitative research approaches was used. Data was collected using a semi-structured interview guide and analyzed thematically to systematically identify, code, and report recurring patterns in a narrative form. It was augmented by a systematic literature review on the life and works of the empiricist philosopher John Locke with a focus on his theory of knowledge. Results A total of 30 participants participated in the study. It was affirmed that knowledge is a distinct attribute proper to human beings. It is obtained through sense experience, reasoning, and revelation from God. However, knowledge is limited and all ideas should be subjected to the criteria of truth and certainty. Conclusion Knowledge is the highest mental and psychological faculty that defines human beings other factors notwithstanding. It is limited in nature although human beings can obtain knowledge sufficient for their functions. It is obtained in many ways including experience, reasoning, and revelation. It should be subjected to proof based on truth and certainty since it cannot be wholly grasped as it is. Recommendation There should be a constant search for knowledge through interactive experiences, reading, and meditation. It requires substantiation based on truth and certainty because it is relative. It should be sought and guarded jealously because it makes human beings unique while fostering a natural tendency toward perfection.